Papillary thyroid carcinoma risk factors in the Yunnan plateau of southwestern China - Zeng R; Shou T; Yang KX; Shen T; Zhang JP; Zuo RX; Zheng YQ; Yan XM (Dove Medical Press, 2016)
Rong Zeng,1–3 Tao Shou,3 Kun-xian Yang,4 Tao Shen,5 Jin-ping Zhang,5 Rong-xia Zuo,5 Yong-qing Zheng,5 Xin-ming Yan5 1Faculty of Environmental Science and Engineering, Kunming University of Science and Technology, Kunming, People’s Republic of China; 2Faculty of Life Science and Technology, Kunming University of Science and Technology, Kunming, People’s Republic of China; 3Medical Oncology, The First People’s Hospital of Yunnan Province, Kunming, People’s Republic of China; 4Surgical Oncology, The First People’s Hospital of Yunnan Province Kunming, People’s Republic of China; 5Institute of Clinical and Basic Medicine Research, The Affiliated Hospital of Kunming University of Science and Technology, Kunming, People’s Republic of China Objective: This study investigated clinical and pathological characteristics and risk factors in papillary thyroid carcinoma (PTC) patients’ native to Yunnan plateau in southwestern China. Methods: Clinical data from 1,198 patients diagnosed with PTC (n=578) and control subjects (n=620) with benign thyroid disease (ie, thyroid nodule disease, benign thyroid diseases [BTD]) in Yunnan province were analyzed retrospectively. Results: The mean patient age was lower for PTC than for BTD. Positive ratios of thyroid peroxidase antibody, thyroglobulin antibody (TGAb), and thyrotrophin receptor antibody (TRAb) were higher in PTC than in BTD patients. The ratio of PTC coexisting with Hashimoto’s thyroiditis (HT) or with lymphocytic thyroiditis was higher than that of BTD. The number of patients whose age at menarche was ≤13 years, who had given birth to less than or equal to two children, or who were in premenopause were higher in the PTC than in the BTD group. Multivariate conditional logistic regression analyses revealed that age >45 years, nodal size >1 cm, and elevated TG levels were protective factors against PTC. Abnormally elevated TGAb and TRAb levels were independent risk factors for PTC in females. Conclusion: HT was not an independent risk factor for but was associated with PTC. TRAb is a risk factor for PTC in individuals living in the Yunnan plateau, but not for those in the plains region. Keywords: papillary thyroid carcinoma, risk factors, Yunnan plateau, benign thyroid disease, autoimmune disease status